Water driven adsorption of amino acids on the (101) anatase TiO2 surface: an ab initio study. Issue 3 (1st December 2014) - Agosta, Lorenzo; Zollo, Giuseppe; Arcangeli, Caterina; Buonocore, Francesco; Gala, Fabrizio; Celino, Massimo
Abstract : Arginine and lysine are stably adsorbed onto the (101) anatase TiO2 surface in water solution. Abstract : Arg, Lys and Asp amino acids are known to play a critical role in the adhesion of the RKLPDA engineered peptide on the (101) surface of the titania anatase phase. To understand their contribution to peptide adhesion, we have considered the relevant charge states due to protonation (Arg and Lys) or deprotonation (Asp) occurring in neutral water solution, and studied their adsorption on the (101) anatase TiO2 surface by ab initio total energy calculations based on density functional theory. The adsorption configurations on the hydrated surface are compared to those on the dry surface considering also the presence of the hydration shell around amino acid side-chains. This study explains how water molecules mediate the adsorption of charged amino acids showing that protonated amino acids are chemically adsorbed much more strongly than de-protonated Asp. Moreover it is shown that the polar screening of the hydration shell reduces the adsorption energy of the protonated amino acids to a small extent, thus evidencing that both Arg and Lys strongly adhere on the (101) anatase TiO2 surface in neutral water solution and that they play a major role in the adhesion of the RKLPDA peptide.